2014
DOI: 10.1371/journal.pone.0110542
|View full text |Cite
|
Sign up to set email alerts
|

Cell Migration Is Regulated by AGE-RAGE Interaction in Human Oral Cancer Cells In Vitro

Abstract: Advanced glycation end products (AGEs) are produced in an irreversible non-enzymatic reaction of carbohydrates and proteins. Patients with diabetes mellitus (DM) are known to have elevated AGE levels, which is viewed as a risk factor of diabetes-related complications. In a clinical setting, it has been shown that patients with oral cancer in conjunction with DM have a higher likelihood of cancer metastasis and lower cancer survival rates. AGE-RAGE (a receptor of AGEs) is also correlated with metastasis and ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…A previous study by our group revealed that AGEs regulate oral cancer cell migration via the ERK signaling pathway (17). The results demonstrated the mechanism by which AGEs regulate p53 via ERK and downstream Nrf-2 and Bcl-xl.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…A previous study by our group revealed that AGEs regulate oral cancer cell migration via the ERK signaling pathway (17). The results demonstrated the mechanism by which AGEs regulate p53 via ERK and downstream Nrf-2 and Bcl-xl.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have demonstrated that cancer malignancy can be promoted by AGEs (14)(15)(16). Furthermore, the migration of oral cancer cells has been revealed to be increased by the receptor for AGEs (17). In a clinical setting, patients with DM exhibit a higher rate of metastasis of oral cancer and a lower cancer-associated survival rate (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that CML might be able to facilitate NSCLC metastasis. Ko et al [17] indicated that AGEs favored invasion and migration of oral cancer cells. Takino et al [14] reported that glyceraldehyde-derived AGEs benefited the migration of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of MMP has been associated with cell migration and metastasis in OSCC [29][30][31]. Thus, AGEs through their influence on MMPs contribute to both tumor aggressiveness and invasive nature of the tumor.…”
Section: Age and Tumor Invasion And Metastasismentioning
confidence: 99%